Validity Evidenceof the Academic Situation-Specific Perceived Self-Efficacy Scale (EAPESA) - Angélica Garzón Umerenkova; Javier Gil Flores; Manuel Rafael de Besa Gutiérrez (Universidad Autónoma de Baja California, 2021)
This study employs a Rasch analysis to present the psychometric properties of the Academic Situation-Specific Perceived Self-Efficacy Scale (EAPESA, in Spanish) in students at a Spanish university. Construct validity, measurement and person reliability, the functioning of the Likert scale, and differential item functioning (DIF) were all explored, producing evidence of discriminant validity in regard to a measurement of academic procrastination and criterion validity in relation to performance. The sample comprised 443 university students from the first to fourth years of three degree programs. Adequate reliability and Likert scale values were found, as was a good fit to the Rasch model. However, evidence was also found to suggest that construct validity could be improved and that DIF by degree program may be present in one item.